Advertising communication of the Geely automobile brand in the media sphere of Belarus and China - Xu, Qi (Journal of the Belarusian State University. Journalism, 2025)
This article examines the advertising strategy of the Geely automobile brand in the media spheres of Belarus and China. It analyses the similarities and differences in the brand’s approaches to promotion in these two markets, as well as the adaptation of its communication strategies to the cultural and social realities of each country. Various communication channels, including digital platforms, traditional media, and event marketing, are examined, as well as the role of local characteristics in shaping the company’s image. Current advertising campaigns, consumer preferences, and market trends are examined, allowing us to draw conclusions about the impact of Geely’s brand advertising strategy on its image and competitiveness in the international arena. It is demonstrated that the brand’s advertising communications in both countries are built with consumer expectations and sociocultural characteristics in mind.